A typological study of mosque internal spatial arrangement: A case study on Malaysian mosques (1700-2007) - Othman, Rosniza; Nila, Inangda; Yahya, Ahmad (Faculty of Built Environment, University of Malaya, 2012)
The paper presents the results of a study on internal design of Malaysian mosques from a typological way of research. Specifically it will look at the form and spatial variety which leads to the functionality of interior space. Orientation of mosques is taken into serious consideration because the prostration activity for Muslims is performed while facing the 'qibla' towards the Ka'bah in Mecca, where the unity of the religion can be seen during the congregational prayers. Apart from that, this typoiogical research will also show clearly the evolution of mosque architecture from the beginning of Islamic embracement in Malaysia. From there, classification of types of mosque design will be defined by analyzing the inner spatial composition and not just by looking at the external built forms. As a result, it is hoped that this paper will help innovate design solutions to the mosque designers and to Muslims who will be using the facility . The typological index produced in this paper will help the present and future generation to learn history through the trend of mosques design evaluation that is shown in the classified images.